Optimal Stopping with Dynamic Variational Preferences - Daniel Engelage (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
We consider optimal stopping problems in uncertain environments for an agent assessing utility by virtue of dynamic variational preferences or, equivalently, assessing risk by dynamic convex risk measures. The solution is achieved by generalizing the approach in terms of multiple priors introducing the concept of variational supermartingales and an accompanying theory. To illustrate results, we consider prominent examples: dynamic entropic risk measures and a dynamic version of generalized average value at risk.
Keywords: C61; C65; D81; 330; Optimal Stopping; Uncertainty; Dynamic Variational Preferences; Dynamic Convex Risk Measures; Dynamic Penalty; Time-Consistency; Entropic Risk; Average Value at Risk; Entscheidung bei Unsicherheit; Suchtheorie; Präferenztheorie; Value at Risk; Zeitökonomik; Theorie